APPLICATION OF COMIC MEDIA TO IMPROVE LEARNING OUTCOMES AND EDUCATIONAL AFFECTIVE STUDENTS ON STRAIGHT MOTION MATERIAL IN CLASS VIII SMP NEGERI 1 DARUL IMARAH ACEH BESAR - Rahmi, Ida -; Rahmati, Rahmati (Phi: Jurnal Pendidikan Fisika dan Terapan, 2019)
Based on the results of observations in the field, most students at SMPN 1 Darul Imarah Aceh Besar school tend to like subjects without mathematics, one of which is art, at the time of observation there were even students who came out of class to make art and chose not science subjects because according to students that science is very complicated. With the presence of comic media it is hoped that it will arouse students' enthusiasm for learning, because comic media is an alternative media for playing while learning. The purpose of this study was to determine whether the application of comic media can improve cognitive and affective learning outcomes of students in straight-motion material in class VIII of SMPN 1 Darul Imarah Aceh Besar. The research method used in this study is to use a quasi-experimental method (Quasi Experiment), with Pre-test and Post-test Control Group Design. Samples were taken from class VIII-4 as an experimental class and class VIII-3 as a control class. Data collection is done by tests and questionnaires. Based on the results of hypothesis testing that has been done, using the t test with a significant level α = 0.05 and dk = 38. The calculation results obtained t_count> t_table is 3.31> 1.68, Based on t test then tcount> tTable, then Ha accepted and H0 rejected, which states that the influence of the use of comic media to improve cognitive and affective learning outcomes of students in the subject of straight motion in class VIII SMP Negeri 1 Darul Imarah Aceh Besar and the response of students Very Agree (SS = 58%), Agree (S = 37.5%), Less Agree (KS = 3%), Disagree (TS = 1%), and Strongly Disagree (STS = 0.5%).